Time-place learning in individually reared angelfish, but not in pearl cichlid - Barreto, Rodrigo Egydio; Rodrigues, Patricia; Luchiari, Ana Carolina; Delicio, Helton Carlos (Elsevier B.V., 2006)
Time-place learning based on food association was investigated in the cichlids angelfish (Pterophyllum scalare) and pearl cichlid (Geophagus brasiliensis) reared in isolation, therefore eliminating social influence on foraging. During a 30-day period, food was placed in one side of the aquarium (containing three compartments) in the morning and in the opposite side in the afternoon. Learning was inferred by the number of correct side choices of all fish in each day of test (15th and 30th). During the test day fish were not fed. The angelfish learned to switch sides at the correct day period in order to get food, suggesting this species has time-place learning ability when individually reared. on the other hand, the same was not observed for pearl cichlid. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: time-place learning; feeding; fish; cichlid